The Implementation of Flipped Classroom to Develop Students' Reading Skill - Jessycha Sania Putri; Neni Nurkhamidah (Universitas Muhammadiyah Kalimantan Timur, 2023)
The objective of this study was to investigate how the implementation of the flipped classroom in improving students' reading skills. This research was conducted using the Classroom Action Research (CAR) method that uses four phases according to the Kemmis and McTaggart model which includes planning, action, observation, and reflection. The subjects of this study were 18 students of class 10 science 1 SMAN 19 Kabupaten Tangerang. The data gathered in this study through observation sheet, interviews, and tests. The findings of the study found that the implementation of the flipped classroom succeeded in improving students' reading skills in which the average score of students who reached the minimum completeness criteria that students obtained an average score of 77.33 in the post-test cycle 2 compared to the pre-test score in which most of the students did not meet the minimum completeness criteria. This study also found that the implementation of the flipped classroom had a positive impact on student learning participation. Keywords: Classroom Action Research; Flipped Classroom; Reading Skills